Using the Kano Model to Analyze the Formation of Regional Attractive Factors of Art Street in Taichung, Taiwan. Issue 2 (1st May 2016) - Chen, Ming-Shih; Ko, Yao-Tsung
Abstract: This research integrated the needs to the regional environments, residents, and tourists to discuss the attractive factors of regional characteristics of the public and private realm. Using Tunghai Art Street as an example, the criteria for regional activation were proposed to shape the tourist attraction with cultural and art characteristics. The preliminary investigation recorded the art installations in Art Street′s pedestrian-only space and Corbusier Square, and observed the tourist behavior and activities in the space. Then, interviews were conducted with the community administrators and tourists, in order to learn their opinions and determine key indicative factors. A questionnaire survey was conducted on the tourists. Meanwhile, the Kano Model, IPA, and ANOVA were employed to discover and analyze the main attractive elements of Art Street. As indicated by research results, the positive comments of interview respondents center on the unique and charming characteristics of stores and the aesthetic and artistic atmosphere of streets, while the negative impressions mostly concerned transportation issues, such as insufficient parking spaces, obstacles on the sidewalks, and difficulty for pedestrians to walk on the sidewalks. Based on the results, this study offered suggestions for improving local activities, public facilities, street landscapes and stores.